An introduction to textile economics - Hirsh, Benjamin Woolf; Ellis, Peter (Manchester : Textile Trade Press, 1973)
This book presents a broad picture covering the economic factors involved in the production of all the main fibres, both natural and man-made, as well as the economics of the principal methods of producing fabrics and clothing.
Includes index.
Bibliography: p. [164]-165.
ijb, 17/01/2019
Loans
Keywords: Textile industry